2019
DOI: 10.3390/jof5010019
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Invasive Candidiasis in Children during a 10-Year Period

Abstract: Candida species are a common cause of invasive infection in neonates and children. The aim of our study was to evaluate the epidemiology and microbiology of invasive candidiasis (IC) in the largest tertiary Greek pediatric hospital during a 10-year period. A retrospective cohort study was performed from January 2008 to December 2017. Identification of species and antifungal susceptibility testing was performed according to the Clinical and Laboratory Standards Institute (CLSI) methodology. During the study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
10
1
Order By: Relevance
“…In particular, it occurred in 3/34 (9%) of C. glabrata SC strains (1/3 was panechinocandin resistant), whereas 1/136 (1%) C. albicans isolates was found to have intermediate susceptibility only to caspofungin. In our literature review, the majority of the recovered Candida isolates were susceptible to echinocandins (94 to 100%) but less so to caspofungin (75 to 100%) (15,17,18,27,(30)(31)(32), contrary to our study, where Ն99% susceptibility to all three echinocandins was found. Since the mono-echinocandin resistance phenotype is rare, the lower caspofungin susceptibility rates found in previous studies where Etest was used may be due to technical issues in MIC reading with this test (52) and the criteria used to interpret the results (53).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In particular, it occurred in 3/34 (9%) of C. glabrata SC strains (1/3 was panechinocandin resistant), whereas 1/136 (1%) C. albicans isolates was found to have intermediate susceptibility only to caspofungin. In our literature review, the majority of the recovered Candida isolates were susceptible to echinocandins (94 to 100%) but less so to caspofungin (75 to 100%) (15,17,18,27,(30)(31)(32), contrary to our study, where Ն99% susceptibility to all three echinocandins was found. Since the mono-echinocandin resistance phenotype is rare, the lower caspofungin susceptibility rates found in previous studies where Etest was used may be due to technical issues in MIC reading with this test (52) and the criteria used to interpret the results (53).…”
Section: Discussioncontrasting
confidence: 99%
“…Fifteen articles reported data from single hospitals and four from multicenter or nationwide studies, whereas in one study, the origin was not reported. The majority of them (12/20; 60%) were performed in intensive care units (ICUs) (3/20 in neonatal/pediatric ICUs [14][15][16] and 9/20 in adult ICUs [17][18][19][20][21][22][23][24][25]), 1/20 in internal medicine wards (IMWs) (26), 2/20 in pediatric patients (27,28), 2/20 in patients with hematological malignancies (29,30), and only 3/20 in the general patient population (all hospital units) (31)(32)(33). Over the years, the most commonly isolated Candida species was C. albicans, with a frequency ranging from 12.5% to 89.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noni et al in their retrospective study including 178 pediatric cases from three neonatal intensive care units, one PICU, two hematology-oncology units, and one bone marrow transplantation unit in Greece reported that the most isolated species were C. albicans and C. parapsilosis. 22 In a study performed on 102 children with nosocomial candidemia in our country between 1997 and 2005, non-albicans Candida species were the most common species. 23 In another single-center study performed on children with malignancy and nosocomial candidemia in our country between 2007 and 2013, non-albicans candidemia was determined in 81.4% of 135 candidemia episodes.…”
Section: Discussionmentioning
confidence: 97%
“…In the United States, invasive candidiasis in the pediatric population mainly occurs in neonates and infants less than one year of age and can often lead to high mortality rates [ 110 ]. Prematurity and admission to the intensive care unit are considered the main predisposing factors for candidiasis [ 111 ]. Prevention against fungal infection in preterm infants can be achieved through antifungal medication, but there are strong concerns over potential adverse effects and the possible emergence of resistant strains [ 112 ].…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%